The Effect of Financial Literacy and Financial Experience on SME Financial Behavior in Indonesia - Purwidianti, Wida; Tubastuvi, Naelati (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
The aim of this study is to examine the effect of financial literacy and financial experience on SMEs financial behavior in Indonesia.The dependent variable is financial behavior while independent variables are financial literacy and financial experience. There are four control variables used, namely company size, business length, age and education level of SME owner. The respondent sample is 42 owners of SMEs in Purwokerto Selatan. This study used multiple regression analysis. The results showed that financial literacy has no effect on financial behavior. Financial experience has a positive effect on financial behavior. While among four control variables, only company size has a significant negative effect on financial behavior. Three control variables have no significant effect on financial behavior. The implication of this study, SME owners have good financial experience will increase financial behavior. Therefore, it is very important to improve the financial experience of SME owners